2005
DOI: 10.1136/bmj.38377.675440.8f
|View full text |Cite
|
Sign up to set email alerts
|

Was Rodney Ledward a statistical outlier? Retrospective analysis using routine hospital data to identify gynaecologists' performance

Abstract: Objectives To investigate whether routinely collected data from hospital episode statistics could be used to identify the gynaecologist Rodney Ledward, who was suspended in 1966 and was the subject of the Ritchie inquiry into quality and practice within the NHS. Design A mixed scanning approach was used to identify seven variables from hospital episode statistics that were likely to be associated with potentially poor performance. A blinded multivariate analysis was undertaken to determine the distance (known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 12 publications
1
34
0
Order By: Relevance
“…The annual publication of national benchmarks enables individuals to compare their own performances with those of their peers before any external audit and, if necessary, to review their practices. Hospital episode statistics data can also identify individuals whose clinical practices may be hazardous and, thus, can be used as an early warning management system [20]. Deviations from the normal range for elective cesarean deliveries may reflect individual obstetric practices; however, deviation from the normal range for emergency cesareans may reflect collective practice.…”
Section: Discussionmentioning
confidence: 99%
“…The annual publication of national benchmarks enables individuals to compare their own performances with those of their peers before any external audit and, if necessary, to review their practices. Hospital episode statistics data can also identify individuals whose clinical practices may be hazardous and, thus, can be used as an early warning management system [20]. Deviations from the normal range for elective cesarean deliveries may reflect individual obstetric practices; however, deviation from the normal range for emergency cesareans may reflect collective practice.…”
Section: Discussionmentioning
confidence: 99%
“…21 Harley et al demonstrated that HES data could have been used to identify Ledward. 22 Worryingly, they also identified 11 other unidentified statistical outliers. Using HES data can, however, only identify problems after they have been happening for a number of years.…”
Section: Professionalism and Revalidationmentioning
confidence: 97%
“…Among the most recent studies on performance are those of Harley et al (2005) in the area of health and Behrenz and Althin (2005) in the area of labor market and unemployment. In Harley et al (2005), the authors have used a two-stage statistical method for evaluating health indicators using routine hospital data to identify gynecologists' performance.…”
Section: Introductionmentioning
confidence: 99%
“…They applied the so-called Malmquist productivity index, which measures the distance from every office to the production frontier and the shifting of the frontier over time. Note that, in Behrenz and Althin (2005), the analysis has been done at the micro level and no consideration have been taken for the possible existence of any hierarchy structure in the data, while in Harley et al (2005), possible hierarchy is taken into account.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation